Pengenalan Lingkungan Kampus Universitas Pamulang Secara Interactive Menggunakan Virtual Tour (VR) Berbasis Website - Muhamad Abdul Aziz; Bobi Agustian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
This study aims to create a website-based virtual tour application that aims to facilitate the introduction of the Pamulang university campus, especially the Viktor campus to prospective students who want to know the location of the campus without having to come to the location. This development research adapts the MDLC (Multimedia Development Life Cycle) development model where this development model has six main stages, namely (1) Concept, is conceptualizing and looking for initial needs for making virtual tour applications, (2) design, is the stage of making a mochup or User Interface that later it will be used in virtual tour applications, (3) collecting material, is stage of collecting datas needed for making this virtual tour application which includes taking 360 pictures and several other assets, (4) assembly is development stage, in this case focusing on Pano2VR application and the Ionic Framework, (5) testing this stage using the Blackbox Testing method, (6) distribution to make it easier for users later, distribution is done by uploading HTML5 files to Hosting.